[~Answer~] (8.):
Heyyy. I'm Avery, and I'm always here to help!
I believe the percent may be 15% ($2,400 - 15% = $2,040)
+++++++++++++++++++++++++++++++++++++++++++++++++++++++++++++++
[~Answer Explanation~}:
The percent of the difference is the rate of the difference * 100%
the percent of the difference = .15 * 100% = 15%
since the new price is less than the old price, that is the percent of the decrease.
(See if it'll work): $2,400- 15% = $2,040
And there's your answer <33
+++++++++++++++++++++++++++++++++++++++++++++++++++++++++++++++
[~Last Messages~}:
<em>Hope this helped you <333
Bye!
</em><u><em>[-!AveryIsSomeHowAlive!-]
</em></u><em>"Just call me and I will be there :)"</em>
Let's pose this question a different way: what are the chances that one out of all possible events is going to happen? What are the chances that, if I roll a die, I will roll a 1, 2, 3, 4, 5, or a 6? What is the probability, if I flip a coin, that the outcome will either be heads or tails? When we take every possible outcome and add their probabilities together, the sum of the probabilities will be 100%, or 1.
Example:
Coin Toss:
Prob of Heads (.5) plus Prob of Tails (.5) = 1
Dice roll:
1/6 (odds of rolling any given number) times 6 (number of possibilities) = 1
So a pentagon is constructed by five identical triangles, that's why you can find the area of one triangle and multiply it with 5:
A_pentagon=A_triangle*5
To find the area of a triangle you must use tangens.
You can watch this for more on that on youtube.
For the length of an arc or a portion of a circle you can find it using:
arc lenght = 2π*r(A/360), where A=angle.
So if you know radians, then 2π is a whole circle. And to calculate for the specific circle you have to use the radius. That's why you multiply with radius, which is the only difference between any two different circles. you then multiply with the part of the circle that you want to find the lenght for, which is A/360 (because there are 360° in a circle)
I hope that helped.
Answer:
7x+21 = 7x + 21
Step-by-step explanation:
7(x+3)=6-(-7x - 15)
L.H.S
=7(x+3)
=7x+21 (multiply 7 by (x+3))
R.H.S:
=6-(-7x - 15)
= 6+7x+15 (multiply the -ive sign in the bracket)
= 7x + 21 ( adding 15 and 6)
now compare the two sides
7x+21 = 7x + 21 hence we prove that L.H.S= R.H.S